Comparative study on the utilization of glass fibers reinforced plastics and laminated steel bars in structural applications using finite Element modeling. (2022) - Narzary, Marjoni; Kumar, Jatinder; Dadra, Sarpreet; Sultan, Umer; Sharma, Shubham; Chohan, Jasgurpreet; Kumar, Raman; Singh, Sandeep
Abstract: The demand of hard Infrastructures like buildings have been changed since last few decades due to various factors like higher load carrying capacity, longer life span, earthquake resistance, utility etc. The construction though steel plays an important role for making stronger and more efficient structures. However, such structures possessed certain drawbacks like corrosion, high repair cost, heavy material, losing its properties at high temperature and it is a product of fossil fuel. Therefore, many researchers have reported their research work to overcome these problems using glass fibre. Thus, observing the advantages of GFRP bars over steel bars, it is considered as one of the alternatives to steel bars. In this study, a simulation analysis was performed using ANSYS software, in which five models Fe250 grade of steel withM40 grade of concrete and other five models of Fe415 grade of steel with M25 grade of concrete were developed and analyzed. During Analysis is performed by replacing the steel bars with Unidirectional Epoxy E-glass rebar's in varying percentage such as 20 %, 40 %, 60 % and 80 % and applying constant load. Analysis results show that replacing of 20 % of main steel bars by glass fibre rebar is considerable. The behaviour of this laminated steel reinforced beam-column joint was properly analyzed. The main steel bars were laminated with Epoxy E-glass fibre layers. The number of layers was 5, each of thickness 0.1 mm. Steel bars were laminated in varying percentage such as 20 %, 40 %, 60 % and 80 %. From the observation of data generated 20 % and 40 % laminated steel reinforced beam-column joint model gave better result than the rest. Calculating their percentage differences, it was found that 40 % lamination of main steel bars by glass fibre layer is more efficient.